Peri‐operative management of the surgical patient with diabetes 2015: Association of Anaesthetists of Great Britain and Ireland. (29th September 2015) - ,; Barker, P.; Creasey, P. E.; Dhatariya, K.; Levy, N.; Lipp, A.; Nathanson, M. H.; Penfold, N.; Watson, B.; Woodcock, T.
Summary: Diabetes affects 10–15% of the surgical population and patients with diabetes undergoing surgery have greater complication rates, mortality rates and length of hospital stay. Modern management of the surgical patient with diabetes focuses on: thorough pre‐operative assessment and optimisation of their diabetes (as defined by a HbA1c < 69 mmol.mol −1 ); deciding if the patient can be managed by simple manipulation of pre‐existing treatment during a short starvation period (maximum of one missed meal) rather than use of a variable‐rate intravenous insulin infusion; and safe use of the latter when it is the only option, for example in emergency patients, patients expected not to return to a normal diet immediately postoperatively, and patients with poorly controlled diabetes. In addition, it is imperative that communication amongst healthcare professionals and between them and the patient is accurate and well informed at all times. Most patients with diabetes have many years of experience of managing their own care. The purpose of this guideline is to provide detailed guidance on the peri‐operative management of the surgical patient with diabetes that is specific to anaesthetists and to ensure that all current national guidance is concordant.